Coping with Spain's Aging : Retirement Rules and Incentives - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2007)
This paper evaluates the macroeconomic and welfare effects of extending the averaging period used to calculate pension benefits in a pay-as-you-go system. It also examines the complementarities between reforms extending the averaging period and those increasing the retirement age under alternative tax policies. The analysis is based on a model in the Auerbach-Kotlikoff tradition applied to the Spanish economy. Without reforms, the simulations suggest that aging-related spending as a share of output will increase 16 percentage points by 2050, which are twice as much as in European Commission (2006) projections due to general equilibrium effects. Also, reforms extending the averaging period to the entire work life limit expenditure pressures at the peak of the demographic shock as much as increasing the retirement age in line with life expectancy (4 percentage points of GDP). These reforms and prefunding the demographic shock mitigate the adverse macroeconomic effects of aging and improve welfare.